ANALISA SISTEM KELISTRIKAN PADA RUANG OPERASI DI TZU CHI HOSPITAL MENURUT STANDAR PERATURAN MENTERI KESEHATAN - Choerudin, Muhammad; Abdi Bangsa, Insani (Aisyah Journal Of Informatics and Electrical Engineering (A.J.I.E.E), 2022)
ABSTRACT The purpose of this study was to determine whether or not the electrical system applied to the operating room at the TZU CHI HOSPITAL hospital was in accordance with the applicable health ministerial regulations. with the qualitative method, data collection is done by means of observation, documentation, and field measurements where the results of the data will be analyzed whether or not it is in accordance with the regulations of the minister of health. The operating room is a vital unit in the hospital, therefore its construction must be in accordance with the design that has been stipulated in the regulation of the minister of health. As in the operating room electrical system, many of the equipment used in the operating room requires electricity and most of the equipment is in direct contact with patients and people around the electrical equipment. So the regulation of the minister of health has stipulated an electrical system that must be applied to every operating room. The results of the research on the electrical system installed in the operating room at TZU CHI HOSPITAL are in accordance with the regulations of the minister of health, where the electrical system already uses an isolator transformer which functions as a safety, so that people in the operating room are not electrocuted when there is a surge. and the main electrical system already uses UPS which functions as backup electricity so that when a power blackout, the electricity in the operating room will remain on. Keywords: UPS; Operating Theater; Electricity System; Minister of Health Regulation ABSTRAK Tujuan penelitian ini yaitu untuk mengetahui sesuai atau tidaknya sistem kelistrikan yang diterapkan pada ruang operasi di rumah sakit TZU CHI HOSPITAL dengan peraturan menteri kesehatan yang berlaku. dengan metode kualitatif, pengambilan data dilakukan dengan cara observasi, dokumentasi, dan pengukuran dilapangan yang mana hasil data akan di analisa sesuai atau tidaknya dengan peraturan menteri kesehatan. Ruang operasi merupakan unit vital yanga ada pada rumah sakit, oleh karena itu pembangunannya harus sesuai dengan desain yang sudah ditetapkan pada peraturan menteri kesehatan. Seperti pada sistem kelistrikan ruang operasi, banyak peralatan yang digunakan pada ruang operasi sebagian besar membutuhkan listrik dan sebagian besar peralatan tersebut berhubungan langsung dengan pasien dan orang disekitar peralatan listrik. Sehingga peraturan menteri kesehatan sudah menetapkan sistem kelistrikan yang harus diterapkan pada setiap ruang operasi. Hasil penelitian sistem kelistrikan yang terpasang pada ruang operasi di TZU CHI HOSPITAL sudah sesuai dengan peraturan menteri kesehatan, dimana pada sistem kelistrikan sudah menggunakan trafo isolator yang berfungsi sebagai pengaman, agar orang yang berada diruang operasi tidak tersengat listrik ketika terjadi lonjakan arus. dan pada sistem kelistrikan utama sudah menggunakan ups yang berfungsi sebagai listrik cadangan sehingga ketika terjadi pemadaman listrik, maka listrik pada ruang operasi akan tetap menyala. Kata Kunci: UPS; Ruang Operasi; Sistem Kelistrikan; dan Permenkes